Regional economic integration and global competition in the post-COVID-19 era European Union, Eurasian economic union, and the Belt and Road Initiative - Shevchenko, Dmitry; Karnaukhova, Oxana (IGI Global, 2022)
"This volume features up-to-date studies and comparison of regional integration efforts of the EU, China, and Russia in Greater Eurasia with the special interest in the complicated relations among the EU, EAEU, and BRI.
Includes bibliographical references and index. - Mode of access: World Wide Web
Keywords: Eurasia -- Economic integration; European Union countries -- Foreign economic relations -- Eurasia; Russia (Federation) -- Foreign economic relations -- Eurasia